2008
DOI: 10.1093/humrep/den081
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of sperm chromatin quality in testicular cancer and Hodgkin's lymphoma patients prior to chemotherapy

Abstract: Sperm DNA integrity and compaction were affected in testicular cancer and Hodgkin's lymphoma patients prior to chemotherapy. Although SCSA, TUNEL and comet assays all detected DNA damage, the latter was optimal for use in cancer patients. A combination of the comet assay with tests that evaluate sperm DNA compaction, such as flow cytometry-based CMA3 and mBBr assays, is a reliable strategy to characterize sperm chromatin quality in cancer patients at the time of sperm banking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
77
4
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(91 citation statements)
references
References 41 publications
8
77
4
2
Order By: Relevance
“…genetic or developmental abnormalities) or due to secondary or extrinsic factors causing testicular or posttesticular injury (e.g. gonadotoxins, hyperthermia, oxidants, endocrine abnormalities) [2][3][4][5][6][7][8][9][10]. Investigators have suggested that protamine deficiency (with aberrant chromatin remodeling), reactive oxygen species (ROS) and abortive apoptosis may cause sperm DNA damage [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…genetic or developmental abnormalities) or due to secondary or extrinsic factors causing testicular or posttesticular injury (e.g. gonadotoxins, hyperthermia, oxidants, endocrine abnormalities) [2][3][4][5][6][7][8][9][10]. Investigators have suggested that protamine deficiency (with aberrant chromatin remodeling), reactive oxygen species (ROS) and abortive apoptosis may cause sperm DNA damage [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…However, it remains uncertain whether the presence of cancer itself could affect sperm DNA integrity in TGCT patients. In fact, although several recent studies reported the increase in sperm DNA damage before treatment in patients with TGCT in reference to fertile controls (Meseguer et al, 2008;O'Flaherty et al, 2008), other studies indicated that DNA fragmentation was not significantly increased in TGCT patients in comparison with the controls (Ribeiro et al, 2008;Smit et al, 2010). The discrepancy between these studies may have been caused by the low numbers of patients studied, or bias in patient and control selections (Smit et al, 2010).…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, apoptotic insults are known to cause SDF (Tamburrino et al 2012;Muratori et al 2015). However, as mentioned above, whether the occurrence of cancer is per se a factor favouring SDF is questioned, because variable results, depending on the type of tumour and on the method used to evaluate the parameter, have been reported (O'Flaherty et al 2008;Meseguer et al 2008;Ribeiro et al 2008;Ståhl et al 2009;McDowell et al 2013). As such, we cannot exclude the possibility that the high postcryopreservation levels of SDF in cancer patients (Edelstein et al 2008;Meseguer et al 2008; present study) reflect damage due to the continuous presence of an altered seminal plasma during the cryopreservation procedure (including the thawing procedure, which lasts several minutes).…”
Section: Discussionmentioning
confidence: 99%
“…However, whether cancer is per se associated with increased SDF remains contentious. For example, in the case of testicular cancer, high levels of SDF have been reported in some studies (O'Flaherty et al 2008;Meseguer et al 2008), but not in others (Ribeiro et al 2008;Ståhl et al 2009;Smit et al 2010). Similarly, elevated SDF levels have been found in samples from men with non-Hodgkin's lymphoma by some (Meseguer et al 2008;Smit et al 2010), but not by others (O'Flaherty et al 2008;McDowell et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation